Expression of CD49f defines subsets of human regulatory T cells with divergent transcriptional landscape and function that correlate with ulcerative colitis disease activity. Issue 9 (6th September 2021) - Weerakoon, Harshi; Straube, Jasmin; Lineburg, Katie; Cooper, Leanne; Lane, Steven; Smith, Corey; Alabbas, Saleh; Begun, Jakob; Miles, John J; Hill, Michelle M; Lepletier, Ailin
Abstract: Objective: Adoptive regulatory T cell (Treg) therapy is being trialled for the treatment of different autoimmune disorders, including inflammatory bowel diseases (IBD). In‐depth understanding of the biological variability of Treg in the human blood may be required to improve IBD immune monitoring and treatment strategies. Methods: Through a combination of quantitative proteomic, multiparametric flow cytometry, RNA‐sequencing data analysis and functional assays on Treg enriched from the blood of ulcerative colitis (UC) patients and healthy controls, we investigated the association between CD49f expression, Treg phenotype and function, and UC disease activity. Results: High‐dimensional analysis and filtering defined two distinct subsets of human Treg based on the presence or absence of CD49f with divergent transcriptional landscape and functional activities. CD49f negative (CD49f − ) Treg are enriched for functional Treg markers and present significantly increased suppressive capacity. In contrast, CD49f high Treg display a pro‐inflammatory Th17‐like phenotype and accumulate in the blood of patients with UC. Dysregulation on CD49f Treg subsets in patients with UC correlate with disease activity. Conclusion: Overall, our findings uncover the importance of CD49f expression on Treg in physiological immunity and in pathological autoimmunity. Abstract : This study defines two distinct subsets of effector regulatory T cells (Treg) circulating in the human blood based on the presence or absence of CD49f with divergent transcriptional landscape and functional activities. CD49f – Treg are enriched for functional Treg markers and present significantly increased suppressive capacity whilst CD49f high Treg display a pro‐inflammatory Th17‐like phenotype and accumulate in patients with ulcerative colitis (UC). Dysregulation of CD49f Treg subsets in patients with UC correlates with disease activity and may be assessed as a way to improve UC immune monitoring.